Kesalahan Kalimat Bahasa Indonesia Siswa Kelas VII SMPN 1 Padang Panjang Tahun Ajaran 2011/2012 - Idewarni .; Harris Effendi Thahar; Ngusman Abdul Manaf (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: The purpose of this study is to describe the terms of the sentence error : (1 ) reasoning , ( 2 ) the structure of the sentence , ( 3 ) diction , and ( 4 ) EYD . The data of this study sentences errors in essay form class VII SMP N 1 Padang Panjang. This research is a descriptive study . The study population class VII SMP N 1 Padang term 2011-2012 . The study population numbered 244 people scattered in seven classes . Given a population of more than 200 students , the sampling technique used is random sampling technique ( random sampling ) , so the population is 50 people . The error rate is calculated based on descriptive statistics . Based on the results of this study concluded that the fault line of reasoning in terms of relatively low ( 9.06 % ) . Sentence structure errors is low ( 11.82 % ) . Diction error is low (13.26 % ) , and EYD error is high ( 65.86 % ) . Kata kunci : kesalahan kalimat bahasa Indonesia.